The Just City - Fainstein, Susan S. (Book collections on Project MUSE., 2010)
In the first half of The Just City, Fainstein draws on the work of John Rawls, Martha Nussbaum, Iris Marion Young, Nancy Fraser, and other to develop an approach to justice relevant to twenty-first-century cities, one that incorporates three central concepts: diversity, democracy, and equity. In the book's second half, Fainstein tests her ideas through case studies of New York, London, and Amsterdam for housing and development in relation to the three norms. She concludes by identifying a set of specific criteria for urban planners and policymakers to consider when developing programs to assure greater justice in both the process of their formulation and their effects."--Pub. desc